Associated factors of depressive symptoms among elderly residents in FELDA scheme in Johor, Malaysia - Hamzah, Nur Aqlili Riana (2017)
Introduction: Elderly might experience depressive symptoms that can be associated with many factors. The objectives of this study were to determine the prevalence of depressive symptoms, characteristics of socio-demographic, psychosocial, health related, functional status, anthropometric parameters and lifestyle characteristics, their correlation with and the associated factor of depressive symptoms among FELDA schemes elderly residents in Johor. Methods: Via cross-sectional study design, 269 respondents (130 men & 139 women) were recruited by systematic sampling with mean age 69.50±5.22 years old. Socio-demographic characteristics were assessed by adapted questionnaire, functional status assessed by using Lawton Instrumental Activity of Daily Living (IADL) Scale, Short Performance Physical Battery (SPPB) questionnaire and Hodkinson Abbreviated Mental Test (HAMT) questionnaire. Physical activity level assessed by Rapid Assessment of Physical Activity (RAPA) questionnaire, anthropometric parameter assessed using anthropometric measurements, energy and nutrients intake assessed by diet history questionnaire and depressive symptoms was assessed by using Geriatric Depression Scale-15 (GDS-15). Results: The prevalence of depressive symptoms was 3.7%. Majority of them were married and have no chewing and vision problem. Many of them disabled in performing 1 or more IADL item, had intermediate level of physical performance and had normal cognitive function. Respondents at younger age and lower monthly income, have disability in performing IADL and lower physical performance, and have lower energy and riboflavin intake were found to have correlation with depressive symptoms. Among all variables, physical performance, energy intake and monthly income found to be the associated factor towards depressive symptoms (R2= 0.081, p<0.05). Conclusion: Depressive symptoms found to have significant correlation with socio-demographic characteristics (age and monthly income), functional status characteristics (IADL and physical performance) and lifestyle characteristics (energy and riboflavin intake). Meanwhile, physical performance, energy intake and monthly income were the associated factor towards depressive symptoms in this study. Further research on nationwide should be done as respondents in this study could act as the model of low depressive symptoms prevalence.